A microspectroscopic insight into the resistivity switching of individual Ag-TCNQ nanocrystals - Rösner, Benedikt; Ran, Ke; Butz, Benjamin; Schmidt, Ute; Spiecker, Erdmann; Fink, Rainer (Physical Chemistry Chemical Physics, 2015)
We investigate the resistivity switching in individual Ag-TCNQ wires with on/off-ratios of up to 103. Raman and soft X-ray absorption microspectroscopy studies disclose reverse charge transfer. Quantifying of the fraction of neutral TCNQ within the switched material yields values up to 22.3%. These findings expedite the understanding of the switching process in Ag-TCNQ nanowires.

Dispersion and characterization of arc discharge single-walled carbon nanotubes-towards conducting transparent films - Rösner, Benedikt; Guldi, Dirk Michael; Chen, J.; Minett, A. I.; Fink, Rainer (Nanoscale, 2014)
This study addresses a combination of a well-developed and mild dispersion method and high-quality arc discharge single-walled carbon nanotubes (SWCNTs) as starting materials. Thus, we advance in fabrication of transparent, conducting films with extraordinary low material loss during SWCNT processing. The starting material was characterized by means of thermogravimetric analysis, high-resolution transmission electron microscopy and Raman spectroscopy. The quality of the starting material and produced dispersions was evaluated by ultraviolet and visible light absorption spectroscopy and Raman spectroscopy. A transparent conductive film was fabricated by drop-casting, whereas films were obtained with electrical to optical conductivity ratios (σ/ σ) as high as 2.2, combined with a loss of nanotube material during processing well below 20 wt%. High pressure carbon monoxide conversion (HiPCO) SWCNTs, which are very well described in the literature, were used for comparison. This journal is © the Partner Organisations 2014.

Employing microspectroscopy to track charge trapping in operating pentacene OFETs - Rösner, Benedikt; Zeilmann, Nina; Schmidt, Ute; Fink, Rainer (Organic Electronics, 2014)
Ultrathin pentacene films resemble benchmark and model materials for organic field-effect transistors (OFETs). We employ scanning transmission X-ray microspectroscopy (STXM) and confocal Raman microspectroscopy as highly resolving probes to obtain insight into the correlation of morphology and charge transport in pentacene OFETs. By combining the operation-induced intensity increase in Raman-active bands with micromorphology, we are able to visualize charge-induced effects, in particular charge trapping in pentacene OFETs during operation. The high sensitivity and specificity of Raman microscopy allows to distinguish between orientation and charge-induced effects and thus to locate the trapped charges at grain boundaries.© 2013 Elsevier B.V. All rights reserved.

In-operando studies of Ag-TCNQ nanocrystals using Raman and soft x-ray microspectroscopy - Rösner, Benedikt; Schmidt, Ute; Fink, Rainer (Journal of Physics: Conference Series, 2017)
We characterize individual Ag-TCNQ nanocrystals during switching their resistivity state in operando. Raman and soft X-ray absorption microspectroscopy are employed to disclose the electronic state of the organic component in dependency of applied voltage. Whereas Raman microspectroscopy offers qualitative insight into the conversion of negatively charged TCNQ molecules to their neutral counterpart, quantification of the neutral fraction can be achieved using X-ray absorption spectroscopy. These results allow a detailed investigation of resistivity switching in electrically bistable Ag-TCNQ nanocrystals.

Nanomorphology in thin films of acetamide end-functionalised quaterthiophene - Zeilmann, Nina; Rösner, Benedikt; Späth, Andreas; Schmidt, Ute; Fink, Rainer (Thin Solid Films, 2015)
<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">α,ω-Functionalised oligothiophenes are promising materials for organic field effect transistors due to their high degree of molecular ordering, crystallinity and π-π stacking. We employ several complementary microspectroscopic probes to investigate the formation of thermally evaporated films of 5,5‴-bis(<em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">N<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">-acetamido-2-ethyl)-2,2′:5′,2″:5″,2‴quaterthiophene on inert substrates. These films were found to grow in a mixed fashion, featuring layer-by-layer domains with thicknesses of several monolayers and needle-shaped three-dimensional crystals. Detailed analysis of atomic force microscopy (AFM) and photoluminescence microscopy reveals the micro- and nanomorphology of the films. Linear dichroism in the near edge x-ray absorption fine structure and polarisation-dependent laser excitation corroborate the findings of AFM, <em style="margin: 0px; padding: 0px; box-sizing: border-box; color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">i.e.<span style="color: rgb(80, 80, 80); font-family: Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", STIXGeneral, "Cambria Math", "Arial Unicode MS", sans-serif; font-size: medium;">, upright standing molecules in the multilayer regime. The shape of the 3-dimensional crystallites and multilayer domains indicates strongly anisotropic growth favoured by the herringbone-arrangement of the thiophene moieties and additional stabilisation by hydrogen bonding of the acetamide end groups.
Keywords: Quaterthiophene; Organic field effect transistor; Confocal Raman microscopy; Near edge x-ray absorption fine structure spectroscopy; Scanning transmission x-ray microscopy

Oxidation-driven self-assembly gives access to high-nuclearity molecular copper vanadium oxide clusters - Forster, Johannes; Rösner, Benedikt; Fink, Rainer; Nye, Leanne; Ivanovic-Burmazovic, Ivana; Kastner, Katharina; Tucher, Johannes; Streb, Carsten (Chemical Science, 2013)
We report a general fragmentation-and-re-assembly route which gives access to high-nuclearity, mixed-metal polyoxometalate clusters. Reduced vanadium(iv) precursors are oxidatively dis-assembled into reactive fragments which subsequently re-aggregate under template control in a one-pot reaction. It is shown that the oxidative dis-assembly is required, as the use of vanadium(v)-based precursors results in the formation of smaller clusters. The principle is exemplified by the synthesis of a ca. 1.8 × 1.7 × 1.0 nm, 36-nuclear copper vanadium oxide cluster, (nBu N)[CuVO(NO )(CHCN)]. The cluster is characterized in the solid-state and in solution by single-crystal XRD, ESI-MS and other spectroscopic and electrochemical measurements. Several lines of evidence show that the compound is indeed formed exclusively by fully oxidized vanadium(v) centres. In addition, primary fragmentation products of the type [VO(dmso)] were isolated. The cuprovanadate cluster features pentagonal secondary building units of the type (V)M (M = Cu, V) which show similar structural function as the well-known (Mo)Mo pentagons observed in giant molybdate clusters. The observation suggests that more complex vanadate clusters might be accessible based on these pentagonal units. © 2013 The Royal Society of Chemistry.

Reversible Photoswitching of a Spin‐Crossover Molecular Complex in the Solid State at Room Temperature - Rösner, Benedikt; Milek, Magdalena; Witt, Alexander; Gobaut, Benoit; Torelli, Piero; Fink, Rainer; Khusniyarov, Marat (Angewandte Chemie, 2015)
Spin‐crossover metal complexes are highly promising magnetic molecular switches for prospective molecule‐based devices. The spin‐crossover molecular photoswitches developed so far operate either at very low temperatures or in the liquid phase, which hinders practical applications. Herein, we present a molecular spin‐crossover iron(II) complex that can be switched between paramagnetic high‐spin and diamagnetic low‐spin states with light at room temperature in the solid state. The reversible photoswitching is induced by alternating irradiation with ultraviolet and visible light and proceeds at the molecular level.
Keywords: molecular switches; photochromism; photomagnetism; spin‐crossover; X‐ray absorption spectroscopy

Switching behaviour of individual Ag-TCNQ nanowires: an in situ transmission electron microscopy study - Ran, Ke; Rösner, Benedikt; Butz, Benjamin; Fink, Rainer; Spiecker, Erdmann (Nanotechnology, 2016)
The organic semiconductor silver-tetracyanoquinodimethane (Ag-TCNQ) exhibits electrical switching and memory characteristics. Employing a scanning tunnelling microscopy setup inside a transmission electron microscope, the switching behaviour of individual Ag-TCNQ nanowires (NWs) is investigated in detail. For a large number of NWs, the switching between a high (OFF) and a low (ON) resistance state was successfully stimulated by negative bias sweeps. Fitting the experimental I-V curves with a Schottky emission function makes the switching features prominent and thus enables a direct evaluation of the switching process. A memory cycle including writing, reading and erasing features is demonstrated at an individual NW. Moreover, electronic failure mechanisms due to Joule heating are discussed. These findings have a significant impact on our understanding of the switching behaviour of Ag-TCNQ.
Keywords: Ag-TCNQ nanowires; in situ transmission electron microscopy; electrical switching; organic memory device; organic electronics

The role of solvation effects in the growth of TCNQ-based charge-transfer salts - Rösner, Benedikt; Späth, Andreas; Fink, Rainer (Journal of Crystal Growth, 2013)
Combining various microscopic techniques (VLM, SEM, STXM) we were able to investigate the growth TCNQ-based charge transfer salts nanocrystals in the wet chemical route. The results unambiguously show the impact of diffusion processes on the formation of Ag-TCNQ nanocrystals to support a modified mechanism for crystal formation. TCNQ-based charge transfer salts represent an attractive class of materials for utilisation in nanoscaled electronic devices. Detailed knowledge about the formation of metal-TCNQ salts is essential to control the growth of well-defined nanostructures. Silver template patterns were used to define well-ordered Ag-TCNQ structures. A comprehensive microscopic and spectroscopic investigation was conducted to examine the growth mechanism in wet-chemical environment in detail. Scanning electron microscopy (SEM) disclosed the overall morphology of the fabricated nanostructures while Scanning Transmission X-Ray Microscopy (STXM) provided insight into the chemical behaviour of the metal cation during the growth. The experimental results give clear evidence that solvation and diffusion of the metal counter ions controls the growth of well-defined metal-TCNQ nanocrystals. © 2013 Elsevier B.V. All rights reserved.

Tuning the light absorption of a molecular vanadium oxide system for enhanced photooxidation performance - Forster, Johannes; Rösner, Benedikt; Khusniyarov, Marat; Streb, Carsten (Chemical Communications, 2011)